Analysis on auger pump performance during handling high viscous liquid - Alisha, E.; Najwa, N.; Jamaludin, A. S.; Razali, M. N. M.; Saffe, S. N. M. (Penerbit UMP, 2022)
Viscosity is one of the factors affecting the performance of the auger pump. An auger pump is positive-displacement (PD) pump that moves fluids and semi-solid material along the screw axis using one or more screws. The study is about the analysis of the performance of the auger pump when transferring various viscosity liquids. In the study, a pumping device with auger shaft is designed. The sample liquids chosen for the experiment oil and concentrated detergent that poses various viscosity. The viscosity is being identified roughly by Zahn Cup Method with the temperature kept constant at 26°C throughout the measurement. The performance of the auger pump can be accessed by altering the motor speed in order to get various reading for the flow rate and pressure. It is found in the study; flowrate is affected by viscosity with the increasing motor speed. The study proves that the auger pump can operate with viscosity of 770 cSt liquid.